2013
DOI: 10.12938/bmfh.32.59
|View full text |Cite
|
Sign up to set email alerts
|

The <i>pyrE</i> Gene as a Bidirectional Selection Marker in <i>Bifidobacterium Longum</i> 105-A

Abstract: We constructed a deletion mutant of the pyrE gene in Bifidobacterium longum 105-A. A pyrE knockout cassette was cloned into pKKT427, a Bifidobacterium-Escherichia coli shuttle vector, and then introduced into B. longum 105-A by electroporation. The transformants were propagated and spread onto MRS plates containing 5-fluoroorotic acid (5-FOA) and uracil. 5-FOA-resistant mutants were obtained at a frequency of 4.7 × 10−5 integrations per cell. To perform pyrE gene complementation, the pyrE gene was amplified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…In this context, it is however noteworthy that, while a Δ thyA strain – promoted as a standard strain for permitting a more versatile and efficient recombination in enterobacteria ( Stringer et al, 2012 ) – was successfully created in the S. enterica strain 14028s ( Stringer et al, 2012 ), we and others were unable to attain a Δ thyA deletion mutant in the context of S. enterica strain SL1344 (personal communication Prof. Joseph Wade (Wadsworth Center, New York, United States of America) and our unpublished observation), which likely indicated its essentiality in this specific S. enterica strain, as thyA was reported among the 343 essential SL1344 genes when grown in rich medium ( Barquist et al, 2013 ). Other metabolic markers broadly used in bacteria ( Fabret et al, 2002 ; Galvao and de Lorenzo, 2005 ; Sakaguchi et al, 2013 ) include E. coli pyrE and pyrF or the B. subtilis pyrE ortholog upp , all implicated in the pathway of pyrimidine synthesis and counter-selectable in strains with the corresponding genetic background (e.g., Δ pyrE , Δ pyrF or Δ upp ). Bacteria harboring a copy of any of these markers are able to grow in the absence of uracil and are sensitive to 5-fluoroorotic acid (5-FOA) given its metabolization to the highly toxic compound 5-fluorouridine monophosphate (5-FMP).…”
Section: Selection and Counter-selection Recombineering Strategiesmentioning
confidence: 99%
“…In this context, it is however noteworthy that, while a Δ thyA strain – promoted as a standard strain for permitting a more versatile and efficient recombination in enterobacteria ( Stringer et al, 2012 ) – was successfully created in the S. enterica strain 14028s ( Stringer et al, 2012 ), we and others were unable to attain a Δ thyA deletion mutant in the context of S. enterica strain SL1344 (personal communication Prof. Joseph Wade (Wadsworth Center, New York, United States of America) and our unpublished observation), which likely indicated its essentiality in this specific S. enterica strain, as thyA was reported among the 343 essential SL1344 genes when grown in rich medium ( Barquist et al, 2013 ). Other metabolic markers broadly used in bacteria ( Fabret et al, 2002 ; Galvao and de Lorenzo, 2005 ; Sakaguchi et al, 2013 ) include E. coli pyrE and pyrF or the B. subtilis pyrE ortholog upp , all implicated in the pathway of pyrimidine synthesis and counter-selectable in strains with the corresponding genetic background (e.g., Δ pyrE , Δ pyrF or Δ upp ). Bacteria harboring a copy of any of these markers are able to grow in the absence of uracil and are sensitive to 5-fluoroorotic acid (5-FOA) given its metabolization to the highly toxic compound 5-fluorouridine monophosphate (5-FMP).…”
Section: Selection and Counter-selection Recombineering Strategiesmentioning
confidence: 99%
“…Among the bifidobacteria, Bifidobacterium longum 105-A ( 7 ), isolated from human feces, has shown exceptionally high transformation efficiency (approximately 10 4 to 10 6 transformants/μg DNA) with several plasmid DNAs ( 6 9 ). Moreover, gene knockout mutants of B. longum 105-A and its derivative strain have been successfully generated using homologous recombination systems ( 8 , 10 12 ). Thus, strain 105-A has become a representative host strain for functional genomics studies of bifidobacteria.…”
Section: Genome Announcementmentioning
confidence: 99%
“…More recently, Ferrario et al examined the amino acid auxotrophy of 52 bifidobacterial strains and revealed that most of them did not grow in a synthetic minimum medium without cysteine [ 2 ]. In addition, most media developed for bifidobacteria so far contain cysteine as a source of sulfur or as a reducing agent [ 3 , 4 , 5 ]. Thus, bifidobacteria have been considered to be cysteine auxotrophs for a long time.…”
mentioning
confidence: 99%
“…longum 105-A ( B. longum 105-A, JCM 31944) [ 9 , 10 ], were routinely cultured in 1/2 MRSCS [ 11 ]. Sulfur-containing amino acid assimilation was examined in bifidobacterial minimal medium (BMM; ingredients provided in Supplementary Table 1 ) [ 5 ] supplemented with 2 mM of cysteine (BMM+Cys) or methionine (BMM+Met), (242 mg/L for cysteine and 298 mg/L for methionine). When DL-homocysteine assimilation was tested, 4 mM of DL-homocysteine (540.7 mg/L) was added to the BMM, as only the L-enantiomer was considered to be utilized.…”
mentioning
confidence: 99%